2022
DOI: 10.2147/rmhp.s341085
|View full text |Cite
|
Sign up to set email alerts
|

Religious Denomination, Religiosity, Religious Attendance, and Cancer Prevention. A Systematic Review

Abstract: Recent research highlighted the influence of religion among health outcomes. To the best of our knowledge, there is no systematic review that summarizes the evidence on the relationship between religious factors and the utilization of cancer screenings. Therefore, this article aims to list the findings about the influence of religious denominations, the importance of religion in one’s life, and religious practices, such as church attendance on the utilization of cancer screenings. PubMed, PsycInfo and CINAHL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Although there may not be existing evidence to confirm that marital status is an independent risk factor for cancer, observational studies demonstrate that married status is associated with reduced risk of cancer-specific and all-cause mortality 27,28 . Religion and spirituality are important in patient cancer care, and specifically, a systematic review suggests a positive association between religious attendance and cancer screening utilization 29 . Our models not only confirmed the significance of these risk factors for each cancer type but also our RF-based model facilitated an interpretable analysis, allowing us to clearly rank the significance of each risk factor, while the MLP-based model provided deeper insights into complex, non-linear interactions among the risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although there may not be existing evidence to confirm that marital status is an independent risk factor for cancer, observational studies demonstrate that married status is associated with reduced risk of cancer-specific and all-cause mortality 27,28 . Religion and spirituality are important in patient cancer care, and specifically, a systematic review suggests a positive association between religious attendance and cancer screening utilization 29 . Our models not only confirmed the significance of these risk factors for each cancer type but also our RF-based model facilitated an interpretable analysis, allowing us to clearly rank the significance of each risk factor, while the MLP-based model provided deeper insights into complex, non-linear interactions among the risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest on the role of S/R practices in cancer prevention. A recent systematic review [ 35 ] evaluated the influence of religious denominations, the importance of religion in one’s life, and religious practices such as church attendance, on the utilization of cancer screenings. Most of the 27 studies included reported a positive association of religious attendance with cancer screening utilization and mixed evidence concerning religious denomination and religiosity.…”
Section: Evidence Of the Association Between Spirituality/religiosity...mentioning
confidence: 99%